Characterization of a SARS-CoV-2 EG.5.1 clinical isolate in vitro and in vivo - Uraki, Ryuta; Kiso, Maki; Iwatsuki-Horimoto, Kiyoko; Yamayoshi, Seiya; Ito, Mutsumi; Chiba, Shiho; Sakai-Tagawa, Yuko; Imai, Masaki; Kashima, Yukie; Koga, Michiko; Fuwa, Noriko; Okumura, Nobumasa; et al. (Cell reports (Cambridge), 2023)
EG.5.1 is a subvariant of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron XBB variant that is rapidly increasing in prevalence worldwide. However, the pathogenicity, transmissibility, and immune evasion properties of isolates of EG.5.1 are largely unknown. Here, we show that there are no obvious differences in growth ability and pathogenicity between EG.5.1 and XBB.1.5 in hamsters. We also demonstrate that, like XBB.1.5, EG.5.1 is transmitted more efficiently between hamsters compared to its predecessor, BA.2. In contrast, unlike XBB.1.5, we detect EG.5.1 in the lungs of four of six exposed hamsters, suggesting that the virus properties of EG.5.1 are different from those of XBB.1.5. Finally, we find that the neutralizing activity of plasma from convalescent individuals against EG.5.1 was slightly, but significantly, lower than that against XBB.1.5 or XBB.1.9.2. Our data suggest that the different virus properties after transmission and the altered antigenicity of EG.5.1 may be driving its increasing prevalence over XBB.1.5 in humans. [Display omitted] •EG.5.1 and XBB.1.5 show similar growth ability and pathogenicity in hamsters•Unlike XBB.1.5, infectious EG.5.1 is detected in the lungs of some EG.5.1-exposed hamsters•Immune-evading properties of EG.5.1 are significantly enhanced relative to those of XBB.1.5 Uraki et al. find infectious EG.5.1, but not XBB.1.5, in the lungs of some variant-exposed hamsters in airborne transmission studies, despite similar growth and pathogenicity between EG.5.1 and XBB.1.5. EG.5.1 also exhibits superior immune-evading properties compared to XBB.1.5.